Inventory of Epiphytes Aquatic Microfungi in Pond of Tailing Bauxite in Tanjungpinang, Bintan Island, Riau Islands Province - Rima Aryani; Tri Apriadi (Journal Omni-Akuatika, 2018)
On the washing process of bauxite mining will produce waste, that was red mud. Those red mud will be streamed in pond of tailing bauxite. Eleocharis sp. has been pioneer plant in pond of tailing bauxite. The objective of this study was identify the epiphytes aquatic microfungi in pond of tailing bauxite, at Tanjungpinang, Bintan Island. Samples were collected by three different stations from Eleocharis sp. density with three samples points in each stations. In this research, the results of epiphyte aquatic microfungi were cultured got five genera and six different species of aquatic microfungi, such as Mucor sp., Curvularia sp. (1 and 2), Phialophora sp., Phoma sp., and Arthrographis sp.Keywords: aquatic microfungi, bauxite, Bintan, Eleocharis sp., tailing